Sequence‐Based Screening of Patients With Idiopathic Polyarteritis Nodosa, Granulomatosis With Polyangiitis, and Microscopic Polyangiitis for Deleterious Genetic Variants in ADA2. Issue 3 (3rd February 2021) - Schnappauf, Oskar; Sampaio Moura, Natalia; Aksentijevich, Ivona; Stoffels, Monique; Ombrello, Amanda K.; Hoffmann, Patrycja; Barron, Karyl; Remmers, Elaine F.; Hershfield, Michael; Kelly, Susan J.; ,; Cuthbertson, David; et al.
Abstract : Objective: Deficiency of adenosine deaminase 2 (DADA2) is a monogenic form of vasculitis that can resemble polyarteritis nodosa (PAN). This study was undertaken to identify potential disease‐causing sequence variants in ADA2 in patients with idiopathic PAN, granulomatosis with polyangiitis (GPA), or microscopic polyangiitis (MPA). Methods: Patients with idiopathic PAN (n = 118) and patients with GPA or MPA (n = 1, 107) were screened for rare nonsynonymous variants in ADA2 using DNA sequencing methods. ADA‐2 enzyme activity was assessed in selected serum samples. Results: Nine of 118 patients with PAN (7.6%) were identified as having rare nonsynonymous variants in ADA2 . Four patients (3.4%) were biallelic for pathogenic or likely pathogenic variants, and 5 patients (4.2%) were monoallelic carriers for 3 variants of uncertain significance and 2 likely pathogenic variants. Serum samples from 2 patients with PAN with biallelic variants were available and showed markedly reduced ADA‐2 enzyme activity. ADA‐2 enzyme testing of 86 additional patients revealed 1 individual with strongly reduced ADA‐2 activity without detectable pathogenic variants. Patients with PAN and biallelic variants in ADA2 were younger at diagnosis than patients with 1 or no variant in ADA2, with no other clinical differences noted. None of the patients with GPA or MPA carried biallelic variants in ADA2 . Conclusion: A subset of patients with idiopathic PAN meet genetic criteria for DADA2. Given that tumor necrosis factor inhibition is efficacious in DADA2 but is not conventional therapy for PAN, these findings suggest that ADA‐2 testing should strongly be considered in patients with hepatitis B virus–negative idiopathic PAN.